2022
DOI: 10.3389/fneur.2022.886567
|View full text |Cite
|
Sign up to set email alerts
|

Glial Dysfunction and Its Contribution to the Pathogenesis of the Neuronal Ceroid Lipofuscinoses

Abstract: While significant efforts have been made in developing pre-clinical treatments for the neuronal ceroid lipofuscinoses (NCLs), many challenges still remain to bring children with NCLs a cure. Devising effective therapeutic strategies for the NCLs will require a better understanding of pathophysiology, but little is known about the mechanisms by which loss of lysosomal proteins causes such devastating neurodegeneration. Research into glial cells including astrocytes, microglia, and oligodendrocytes have revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 140 publications
(146 reference statements)
0
20
0
Order By: Relevance
“…Electron microscopy revealed that granular osmiophilic deposits (GROD, abnormal lysosomal structures) and abnormal autophagic structures accumulated in the neurons of CtsD flox/flox ; Nestin‐Cre mice (Suzuki et al, 2022). Furthermore, activated astrocytes and microglia are increased in the brains of CtsD flox/flox ; Nestin‐Cre mice, as is the case in other NCL mouse models (Takahashi et al, 2022). However, the morphological association of SQSTM1/p62‐positive signals and GRODs in activated glial cells of CtsD flox/flox ; Nestin‐Cre mice has not been studied because of the difficulty in identifying the complicated ultrastructure of activated microglia and astrocytes in the brain (Savage et al, 2018).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Electron microscopy revealed that granular osmiophilic deposits (GROD, abnormal lysosomal structures) and abnormal autophagic structures accumulated in the neurons of CtsD flox/flox ; Nestin‐Cre mice (Suzuki et al, 2022). Furthermore, activated astrocytes and microglia are increased in the brains of CtsD flox/flox ; Nestin‐Cre mice, as is the case in other NCL mouse models (Takahashi et al, 2022). However, the morphological association of SQSTM1/p62‐positive signals and GRODs in activated glial cells of CtsD flox/flox ; Nestin‐Cre mice has not been studied because of the difficulty in identifying the complicated ultrastructure of activated microglia and astrocytes in the brain (Savage et al, 2018).…”
Section: Introductionmentioning
confidence: 73%
“…Electron microscopy revealed that granular osmiophilic deposits (GROD, abnormal lysosomal structures) and abnormal autophagic structures accumulated in the neurons of CtsD flox/flox ; Nestin-Cre mice (Suzuki et al, 2022). Furthermore, activated astrocytes and microglia are increased in the brains of CtsD flox/flox ; Nestin-Cre mice, as is the case in other NCL mouse models (Takahashi et al, 2022).…”
Section: Introductionmentioning
confidence: 74%
“…Localized glial activation of both astrocytes and microglia is another pathological hallmark of NCLs, including CLN2 disease (37). To assess whether interneuron-specific TPP1 deficiency triggers glial activation, we performed immunohistochemistry on brain sections of 15-week-old Vgat-Cre; TPP1LAMP1 mice for glial fibrillary acidic protein (GFAP), a marker for astrogliosis, and CD68, a marker for microglial activation (37, 38). Immunohistological analysis revealed a marked increase in both GFAP and CD68 immunoreactivities in age-matched Cln2 R207X/R207X mice across CPu, S1BF, and VPM/VPL, but no significant increase was observed within any of these brain regions of Vgat-Cre; TPP1LAMP1 mice compared to age-matched TPP1LAMP1 mice (Figure 3A and B).…”
Section: Resultsmentioning
confidence: 99%
“…53 We examined hallmark neuroinflammation in brain regions known to be involved in Batten pathogenesis, namely the ventral posterolateral and ventral posteromedial nuclei (VPM/VPL) of the thalamus, the somatosensory cortex barrel field (S1BF), the CA3 region of the hippocampus, and the dentate gyrus (DG) and hilus regions of the hippocampus. [74][75][76] In Cln2 R207X mice, treatment with AF38469 (0.3 μg/ml) slightly reduced levels of mitochondrial ATP synthase subunit C (SubC), a primary constituent of the lysosomal storage material, in the S1BF of the somatosensory cortex, CA3 of the hippocampus, and VPM/VPL of the thalamus (Figure 3D-F). 77 Cln2 R207X mice treated with AF38469 had reduced levels of microglial reactivity (CD68 + ) in the VPM/VPL of the thalamus while no impact was observed in other regions (Figure 3F).…”
Section: Resultsmentioning
confidence: 99%